Asuhan Kebidanan Komprehensif Pada Ny. F Umur 30 Tahun Dengan Kekurangan Energi Kronik Di Puskesmas Kaliwadas Kabupaten Brebes Tahun 2023 - Irfatul Adzkiyah; Hafsah Hafsah; Sri Mulyani (Jurnal Medika Nusantara, 2024)
The maternal mortality rate in the world is about 303,000 out of 91.45/100,000 KH (WHO, 2022). In ASEAN, the maternal mortality rate in developing countries is 239 per 100,000 (ASEAN Secretariat, 2022). In Indonesia, the maternal mortality rate in 2022 is 305/100,000 KH (Indonesian Ministry of Health, 2022). In Central Java Province, the maternal mortality rate in 2022 was 98.6/100,000 KH (Central Java Health Office, 2022). In Brebes Regency, the maternal mortality rate in 2022 was around 105 cases (Brebes Health Office, 2022). Kaliwadas Health Center in 2022 recorded 1 case of maternal mortality (Health Profile of Kaliwadas Health Center in 2022). Provide comprehensive midwifery care for pregnant women, maternity, newborns, postpartum and family planning (KB) using the Varney and SOAP management approaches. Research Methods: The method used in this research is a qualitative descriptive method with a comprehensive case study approach. Pregnancy midwifery care that has been given to Mrs. F aged 30 years with Chronic Energy Deficiency has been given management according to the needs of the mother, but Mrs. F still experiences SEZ until delivery. In labor, newborn, postpartum until family planning Mrs. F did not have complications and there were no gaps between theory and practice. Comprehensive midwifery care given to Mrs. F with Chronic Energy Deficiency (SEZ) has been carried out in accordance with Standard Operating Procedures (SOP) with the condition of the mother and baby is good.